## Math Problem Statement

How would I solve this equation? [(x^(2/3)) - (5x^(1/2)) + 6 = 0]

## Solution

## Ask a new question for Free

### By Image

Drop file here or Click Here to upload

## Math Problem Analysis

### Mathematical Concepts

Algebra

Polynomials

Substitution Method

Exponents

### Formulas

x^(2/3) = y^4

x^(1/2) = y^3

Factoring y^4 - 5y^3 + 6 = (y^2 - 2)(y^2 - 3)

### Theorems

Factoring Polynomial Theorem

Exponent Rules

### Suitable Grade Level

Grades 10-12

## Related Recommendation

Solve Equation with Fractional Exponents: x^(2/3) - 5x^(1/3) + 6 = 0

Solve the Equation x^(4/3) - x^(2/3) - 5 using Substitution and the Quadratic Formula

Solving x^(3/5) + x^(1/5) - 6 = 0 Using Substitution

Solving the Polynomial Equation x^6 - 5x^3 - 6

Solve the Equations Involving x^(2/3) and x^4 with Exact Form Solutions